Mudanças e permanências na carreira do Magistério Estadual do Pará: 1986-2010 - FERREIRA, Denielson Moura (Universidade Federal do Pará, 2017)
This study analyses the career of the public school body of Pará in the perspective of examining the changes and continuities from Law 7.442/2010, which provides for PCCR/2010 (Offices, Career and Remuneration Plan). It was assumed a definition of career based on the idea that a teacher’s professional trajectory must be followed by an improvement in pay based on factors like time, performance and initial and continuing formation. Through file research using sources like Law 5.351/1986, which approved the School Body Statute; and Law 7.442/2010, which approved PCCR/2010; were analyzed the changes and continuities of the teachers’ career through 5 axis: office structure, job admission ways, working hours, job progression criteria and pay. With PCCR career is structured in four classes (I through IV), corresponding to formation of higher education, specialization, master and doctorate, with previous positions extinct. Ways of job admittance were kept, but their requirements changed. The working hours changed in composition through the raise of the time-activity percentage from 20% to 25%. Career movement through horizontal and vertical progress was kept, but the criteria of horizontal progress and the salary increase percentage were changed, introducing the budgetary situation of the State as condition to career evolution. As for pay, it was defined a 30% raise for teachers who worked on Special Education, plus the creation of rewards for teachers working on SUSIPE (Superintendence of Criminal Justice System), FUNCAP (Children and Adolescents Institute) and SOME (Modular Education System). The changes and continuities observed after PCCR/2010 portrait the interconnection of powers in the historic moment, permeated in fights of education workers and the government; and, like any political process, it shows partial results to the evaluation of education professionals of Pará.